Severe Hydronephrosis and Dysuria-Hematuria Syndrome after 20 Years of Bladder Exstrophy Correction: A Case Report - Emanuela Altobelli; Alfredo Maria Bove; Federico Sergi; Marzio Angelo Zullo; Maurizio Buscarini (Case Reports in Urology)
The aim of this paper is to report a case of severe hydronephrosis and incontinence 20 years after bladder exstrophy repair, managed successfully by secondary ureteroneocystostomy and by transurethral submucosal injection of Macroplastique.